DNA-based hydrogels for bone regeneration: A promising tool for bone organoids - Xiang Wu; Yan Hu; Shihao Sheng; Huijian Yang; Zuhao Li; Qinglin Han; Qin Zhang; Jiacan Su (Materials Today Bio)
DNA-based hydrogels stand out for bone regeneration due to their exceptional biocompatibility and programmability. These hydrogels facilitate the formation of spatial bone structures through bulk hydrogel fabricating, microsphere formatting, and 3D printing. Furthermore, the bone microenvironment can be finely tuned by leveraging the degradation products, nanostructure, targeting, and delivery capabilities inherent to DNA-based materials. In this review, we underscore the advantages of DNA-based hydrogels, detailing their composition, gelation techniques, and structure optimization. We then delineate three critical elements in the promotion of bone regeneration using DNA-based hydrogels: (i) osteogenesis driven by phosphate ions, plasmids, and oligodeoxynucleotides (ODNs) that enhance mineralization and promote gene and protein expression; (ii) vascularization facilitated by tetrahedral DNA nanostructures (TDNs) and aptamers, which boosts gene expression and targeted release; (iii) immunomodulation achieved through loaded factors, TDNs, and bound ions that stimulate macrophage polarization and exhibit antibacterial properties. With these advantages and properties, these DNA-based hydrogels can be used to construct bone organoids, providing an innovative tool for disease modeling and therapeutic applications in bone tissue engineering. Finally, we discuss the current challenges and future prospects, emphasizing the potential impacts and applications in regenerative medicine.